2013
DOI: 10.1093/cid/cit271
|View full text |Cite
|
Sign up to set email alerts
|

Models of Care for the Management of Hepatitis C Virus Among People Who Inject Drugs: One Size Does Not Fit All

Abstract: One of the major obstacles to hepatitis C virus (HCV) care in people who inject drugs (PWID) is the lack of treatment settings that are suitably adapted for the needs of this vulnerable population. Nevertheless, HCV treatment has been delivered successfully to PWID through various multidisciplinary models such as community-based clinics, substance abuse treatment clinics, and specialized hospital-based clinics. Models may be integrated in primary care--all under one roof in either addiction care units or gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(145 citation statements)
references
References 50 publications
6
137
0
2
Order By: Relevance
“…community health centres, OST clinics, primary care) (Bruggmann & Litwin, 2013). In Canada, several successful HCV care models have been developed in Victoria (Milne, this issue) and Toronto (Mason, this issue) within community health centres with extensive health care and other services targeted for PWID.…”
Section: Epidemiology and Prevention Of Hcv Infection Among Pwidmentioning
confidence: 99%
See 1 more Smart Citation
“…community health centres, OST clinics, primary care) (Bruggmann & Litwin, 2013). In Canada, several successful HCV care models have been developed in Victoria (Milne, this issue) and Toronto (Mason, this issue) within community health centres with extensive health care and other services targeted for PWID.…”
Section: Epidemiology and Prevention Of Hcv Infection Among Pwidmentioning
confidence: 99%
“…This study demonstrates that a multi-disciplinary, community-based model of HCV treatment can improve the lives of PWID in ways that extend beyond HCV. The common theme from this spectrum of HCV care models among PWID, is that ''one size does not fit all'' (Bruggmann & Litwin, 2013). When barriers are systematically addressed within a supportive environment, HCV assessment and treatment among PWID can be very successful.…”
Section: Epidemiology and Prevention Of Hcv Infection Among Pwidmentioning
confidence: 99%
“…Coupling these with initiatives to enable access to affordable, quality screening and treatment is key to curtailing the epidemic among PWID. Prevention and access campaigns are increasingly important to control unsafe injection-associated infections, as the illicit nature and associated marginalisation of PWID populations make them hard to reach for conventional healthcare providers [14,34]. A recent review outlines the need for social interventions relating to housing, stigma reduction and systemic changes in policy and health care delivery in order to improve access and uptake of hepatitis C treatment among PWID [35].…”
Section: Discussionmentioning
confidence: 99%
“…Successful models of integration of HCV care within different services have been documented, including opioid substitution clinics, general practitioner clinics, prisons, and secondary/tertiary care settings. (Bruggmann andLitwin, 2013, Lloyd et al, 2013) Service integration has been found to lead to improved patient outcomes in other areas, including HIV and TB, maternal, new-born, and child health services. (Suthar et al, 2014) Considering the high rates of HIV/HCV coinfection in some settings, integration of HCV-related services, as well as service for other common health concerns faced by people who inject drugs, into existing HIV programmes for people who inject drugs is a clear way to increase access to treatment, and this strategy is endorsed by WHO.…”
Section: Integration Of Servicesmentioning
confidence: 99%